Research Trends of SDGs Integrated Science Interactive Learning Media to Improve Students' Science Literacy: Bibliometric Analysis - Ferniawan Ferniawan; Agus Ramdani; Joni Rokhmat; A Wahab Jufri; AA Sukarso (Postgraduate, University of Mataram, 2025)
This study examines the trend of interactive science learning media integrated with SDGs to improve students' science literacy. Improving science literacy is considered important considering the complexity of global challenges that require scientific understanding in sustainable decision-making. This study aims to provide a bibliometric review of publications related to interactive science learning media integrated with SDGs to improve students' science literacy during the period 2015-2024. Data were collected from Google Scholar using analysis tools such as Publish or Perish and Dimension.ai, resulting in 1,000 documents identified and selected using the PRISMA guidelines. The analysis was carried out using bibliometric and content analysis methods, supported by VOSviewer software to visualize keyword trends and emerging research patterns. The results show a significant increase in the trend of publications of interactive science media integrated with SDGs, with a peak in 2023. The dominance of keywords such as